Unintentional common carotid artery cannulation during attempted internal jugular venous catheter insertion: Nenamerna kateterizacija skupne karotidne arterije pri poskusu vstavitve centralnega venskega katetra v notranjo jugularno veno - Janež, Jurij; Marksl Janež, Dragica (Acta Medico-Biotechnica, 2021)
Purpose: Insertion of a central venous catheter is a common procedure, performed by anesthesiologists and other medical professionals. The preferred site for central venous cannulation is the right internal jugular vein.Case Report: We present the case of a male patient who underwent renal transplantation for end-stage renal disease. During preparation for surgery, the right common carotid artery was cannulated instead of the right internal jugular vein. The situation was immediately recognized and managed by a vascular surgeon. The patient recovered completely without neurological deficit.Conclusion: Central venous cannulation is usually performed using the landmark technique. Incidental cannulation of the common carotid artery is a rare complication that can have serious consequences if not immediately recognized and properly managed.
Keywords: central venous catheter placement; incidental artery cannulation; complications; ultrasound guidance